STUDI ETNOZOOLOGI DI SUB DAS MENDALAM SEKITAR KAWASAN TAMAN NASIONAL BETUNG KERIHUN KAPUAS HULU - Angreani, Angela; Prayogo, Hari; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2020)
Local communities around Betung Kerihun National Park, especially people who live around the Mendalam River, still use forest resources. One of them is fauna. One of the ethnic communities in the Mendalam River in a Datah Diaan village is Dayak Kayaan and Dayak Punan Bukat. Utilization and use of these animals by the local community has become a tradition for the generations. The people who live around the Mendalam River use a lot of wild animals around them because their residence is surrounded by forests which are still good or protected. This research aims to collect the data of types of animals, which are used by indigenous people in the Mendalam River in their daily lives. This research was conducted by using survey method and the respondents were taken by using snowball sampling. The results showed that there were 85 species of animals that were used by Dayak Kayaan and Dayak Punan Bukat community. Based on grade level, there were 8 classes of animals used, namely Mammals, Amphibians, Aves, Molluscs, Pisces, Reptiles, Insects and Crustaceans, and the most used animals were from the pisces class which consists of 26 types and at least 1 amphibian was used. These animals were used for various needs such as for consumption, treatment, supernatural or mystical, omens, artistic value, and others. The most used animal was for consumption as much as 50%, for treatment was 25%, for ritual or mystical or omens was 15%, for art was 5%, and the use of animals for other was 5%. Keywords: Dayak Kayan, Dayak Punan Bukat, Ethnozoology